Literature Review: Korelasi Kadar Malondialdehid dengan Ansietas Pada Lanjut Usia - Muhammad Ramazali; Fakhrurrazy Fakhrurrazy; Fujiati Fujiati (Homeostasis, 2021)
Abstract: The global population of elderly is estimated continue to increase every year. Elderly can get various kinds of physical and psychological disorders related to the degenerative process. One of the disorders that can be occur by elderly is anxiety disorder. Pathogenesis of anxiety is still unclear, but it is believed to be the accumulation of various factors such as environmental influences, life experiences, problematic mindset, genetics and oxidative stress. One of the oxidative stress marker compounds that are often associated with anxiety is malondialdehyde. Through this literature review, the author aims to provide an explanation of the correlation between malondialdehyde levels and anxiety in elderly. Writing this review performed with analyzing related literature obtained from search results on databases in Google Scholar, PubMed, and Science Direct for the last 20 years (2000-2020). The results of this literature review show a correlation between malondialdehyde levels and anxiety in elderly. Keywords: malondialdehyde, anxiety, elderly, oxidative stress Abstrak: Populasi lanjut usia(lansia) secara global diperkirakan akan terus mengalami peningkatan setiap tahunnya. Lansia dapat mengalami berbagai macam gangguan fisik maupun psikis yang berkaitan dengan proses degeneratif. Salah satu gangguan yang dapat dialami lansia adalah gangguan ansietas. Patogenesis ansietas masih belum jelas, namun diyakini merupakan akumulasi berbagai macam faktor seperti pengaruh lingkungan, pengalaman hidup, pola pikir yang bermasalah, genetik dan stres oksidatif. Salah satu senyawa penanda stres oksidatif yang sering dikaitkan dengan kejadian ansietas adalah malondialdehid (MDA). Melalui literature review ini, penulis bertujuan untuk memberikan penjelasan mengenai korelasi kadar MDA dengan ansietas pada lansia. Penulisan review ini dilakukan dengan menganalisis literatur terkait yang didapatkan dari hasil pencarian pada database berupa Google Scholar, PubMed, dan Science Direct selama 20 tahun terakhir (2000–2020). Hasil dari literature review ini terdapat korelasi antara kadar MDA dengan ansietas pada lansia. Kata-kata kunci: malondialdehid, ansietas, lansia, stres oksidatif